2011
DOI: 10.3354/ame01540
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton are more tolerant to UV than ­bacteria and viruses in the northern South China Sea

Abstract: In late summer of 2005, the effects of ultraviolet radiation (UVR) on primary production (PP), bacterial production (BP) and viral decay rates (VDR) were investigated along a salinity gradient in the northern South China Sea. The freshwater input increased the UVA diffuse attenuation coefficient (up to 2.7 m −1 ) near the Pearl River estuary and consequently influenced the UVR inhibitory effects, as VDR was significantly correlated with the UVA diffuse attenuation coefficient. UVR inhibition of PP was signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 65 publications
0
8
1
Order By: Relevance
“…In addition, a higher sensitivity to UVR was found for epilimnetic phytoplankton than for bacteria mainly under subsurface conditions, suggesting that photosynthetic processes are more sensitive under extreme conditions that mimic the global-warming scenario. This result contrasts with previous reports of greater UVR damage to bacterioplankton than to phytoplankton in oligotrophic waters of the Mediterranean Sea (Bertoni et al, 2011), the northern South China Sea (Yuan et al, 2011), high-mountain lakes (Sommaruga et al, 1997), and boreal lakes (Xenopoulos and Schindler, 2003).…”
Section: Sensitivity Of Phytoplankton and Bacteria To Uvr And Stratifcontrasting
confidence: 56%
“…In addition, a higher sensitivity to UVR was found for epilimnetic phytoplankton than for bacteria mainly under subsurface conditions, suggesting that photosynthetic processes are more sensitive under extreme conditions that mimic the global-warming scenario. This result contrasts with previous reports of greater UVR damage to bacterioplankton than to phytoplankton in oligotrophic waters of the Mediterranean Sea (Bertoni et al, 2011), the northern South China Sea (Yuan et al, 2011), high-mountain lakes (Sommaruga et al, 1997), and boreal lakes (Xenopoulos and Schindler, 2003).…”
Section: Sensitivity Of Phytoplankton and Bacteria To Uvr And Stratifcontrasting
confidence: 56%
“…For instance, bacterial production in oligotrophic marine waters was inhibited by sunlight to a greater extent than in coastal waters influenced by the discharge of less transparent nutrient-rich freshwater (Joux et al, 2009). By contrast, no clear patterns were observed in bacterial responses to UV exposure despite the differences in optical and chemical properties along a transect from estuarine to offshore waters (Yuan et al, 2011). …”
Section: Scales Of Variability In the Exposure Of Aquatic Microbes Tomentioning
confidence: 99%
“…Despite a rising number of studies have shown that sunlight is a major cause of viral destruction (Suttle and Cheng, 1992; Noble and Fuhrman, 1997; Jacquet and Bratbak, 2003; Wilhelm et al, 2003; Yuan et al, 2011), to our knowledge no direct evidence is available for an associated enhancement of bacterial abundance or activity in natural waters. In contrast, exposure to surface UVR levels was shown to cause an increase in damaged prokaryotic cells and an accumulation of viruses, probably due to UVR induction of the lytic cycle in lysogenic bacteria (Maranger et al, 2002).…”
Section: Causes Of Variability In Bacterial Responses To Sunlightmentioning
confidence: 99%
“…Predicting the effect of UV radiation (UVR) on plankton metabolic balance is cumbersome because, in addition to its direct effects on the inhibition and reduction of photosynthetic and community respiration rates, metabolic imbalances may derive from differential sensitivities to UVB among planktonic organisms within the community (De Lange et al 2003;Yuan et al 2011). Additionally, photochemical transformations of dissolved organic matter (DOM) mediated by UVR (Zepp et al 2007) can influence the availability of DOM to bacteria (Tranvik and Bertilsson 2001), potentially increasing respiration rates.…”
mentioning
confidence: 99%